PELAKSANAAN DESA SIAGA STRATA PRATAMA TAHUN 2016 (Studi Kasus Desa Siaga Wilayah Kerja Puskesmas Jetis Kabupaten Ponorogo) - Levy Karunia Putri; Setiawan .; Mamik . (GEMA LINGKUNGAN KESEHATAN, 2017)
ABSTRACTDesa Siaga is a government program in an effort to get closer to basic health services to villagers, toalert communities in facing health problems, to make the communities independent in developing clean andhealthy living behavior. However, Desa Siaga program did not meet the expectation. The purpose of thisstudy was to investigate the implementation of Desa Siaga Pratama stage in Jetis health center work area.This is a descriptive research. The data was collected by interview about eight criteria for appointingDesa Siaga Aktif with research object include the chairman, village midwives, health workers, and 6members of community in each village. The data obtained were processed by using Microsoft Office Excel.The results showed that of 14 Desa Siaga, Jetis sub district, 11 villages were categorized as Pratamastage, while the 3 villages could not be defined, meaning that the general purpose of Desa Siaga, which is tocreate community that care and responsive in addressing health problems independently there, was not met.Government and health center should improve monitoring to the development of Desa Siaga Aktif. Itis also advisable to establish UKBM to create independent community to prevent and manage healthproblems. In addition, budgeting through the village budget to support Desa Siaga activities will be also agood step to be implemented. It is advisable for the community to play an active role to support all theactivities in order to create Desa Siaga in Jetis sub district.Keywords : Implementation of Alert Village, 8 indicators, the staging of Desa Siaga